Tuberculosis in foreign students in Japan, 2010–2014: a comparison with the notification rates in their countries of origin - Ota, Masaki; Uchimura, Kazuhiro; Kato, Seiya (Western Pacific Surveillance and Response, 2016)
Japan is currently facing the challenge of tuberculosis (TB) in immigrants. To assess the risk of TB in immigrants to Japan, we reviewed TB in foreign-born students registered from 2010 through 2014 and compared the notification rates for students of each country in Japan with those in their home countries. There were 1128 cases of foreign-born students with TB from 2010 through 2014, of whom 688 (61.0%) were males, with a median age of 23 years. The majority (86.7%) were from 18 to 27 years old. Of these students with TB, 530 (46.9%) were from China, followed by Vietnam (131, 11.6%) and Nepal (127, 11.2%). The notification rates for foreign-born students with TB were highest for the Philippines (675/100,000 person-years [PYs], 95% confidence interval [CI]: 372-977), followed by Myanmar (617/100,000 PYs, 95%CI: 417-817) and Nepal (498/100,000 PYs, 95%CI: 385-611). The notification rates for TB in the students from certain countries were much higher (the Philippines, Myanmar, Nepal, Mongolia, Indonesia, Vietnam, and China) or lower (Republic of Korea and Taiwan) than those in the countries themselves. This is believed to be the first report on TB in an immigrant subpopulation in Japan, particularly with regard to comparisons of TB notification rates in the immigrant population with those of their home countries. Based on our findings, we believe that, for assessing the TB risk in immigrants to Japan, the notification rate for foreign-born students is more useful and accurate as a measure than the TB notification rates in their countries of origin.